The role of dentists in the diagnosis and treatment of oral condyloma acuminatum in children (Research, Society and Development, 2024)
Papules and warts are clinical manifestations of the oral condyloma acuminatum, which is caused by human papillomavirus types 6 and 11 and transmitted through orogenital contact or autoinoculation. The objective of the present study is to conduct an integrative literature review with  retrospective analytical study selected clinical cases and other research on oral condyloma acuminatum in children published between 2013 and 2023 in the Pubmed, Web of Science, VHL, Google Scholar, Proquest, and ScienceDirect databases, using the descriptors "oral condyloma acuminatum" AND "child abuse" AND "condyloma acuminatum". Eighteen articles were selected after applying inclusion and exclusion criteria. The reported association between condyloma acuminatum in children and sexual abuse varied between 10% to 90%. The lesions were mostly observed in females and usually occurred on oral mucosa and floor, gums, tonsils, and palate. Diagnosis is based on clinical examination, histological observation, and hybridization. Treatment may involve surgical removal with scalpels, laser, cryotherapy, and topical medications such as imiquimod and podophyllotoxin. The role of dentists in the clinical diagnosis and histopathological analysis of oral mucosal lesions must be emphasized.